Chemical combination for producing ceramic dispersions or ceramic
By using a combination of ceramic chemicals with crosslinked polymers with chelated functional groups as binders, the problems of cracks and discoloration in the production of ceramic molded parts are solved, and high-quality, low-color discoloration of ceramic molded parts are achieved, improving the production of high-quality, low-color discoloration of ceramic molded parts Mechanical properties and stability.
Patent Information
- Application Number
- CN202380043071.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-27
- Filing Date
- 2023-05-27
- Publication Date
- 2025-01-07
AI Technical Summary
In the existing production methods of ceramic molded parts, cracks and bubble defects are prone to occur during layer-by-layer construction, and the use of free radical polymers will damage other components of the composition, resulting in discoloration and poor mechanical properties and limited stability.
Using a chemical combination including a preferred powdered ceramic material and a gelling agent with chelating functional groups, a high viscosity ceramic suspension or gel is formed by crosslinking polymers as a binder to ensure uniform distribution and stability of the ceramic particles. Avoid settlement and use cross-linked polymers and super-water-absorbent polymers to improve the processability and stability of the material.
Achieve the construction of ceramic molded parts without concurrency problems, obtain high-quality, low-color distortion ceramic molded parts, reduce edge shrinkage during degumming and sintering, improve mechanical properties and durability, and ensure the stability of ceramic materials. and processability.
Smart Images

Figure CN119278190A_ABST
Abstract
Description
[0001] Subject matter of the invention
[0002] The present invention relates to a chemical combination for producing ceramic dispersions or ceramic gels, which in turn are suitable for producing ceramic moldings, such as ceramic coverings or moldings, for example ceramic partial crowns, veneers, ceramic inlays and ceramic onlays, preferably by a layer-by-layer construction method (e.g. stereolithography). The invention also relates to a method for producing ceramic moldings and ceramic moldings produced by the method. Background of the Invention
[0004] In a layer-by-layer construction method for producing ceramic coverings or molded bodies, a ceramic gel or ceramic dispersion with a (curable) polymer material is applied layer by layer to a substrate and simultaneously or subsequently dried, for example by the action of radiation or heat. Thus, a so-called ceramic "green body" is obtained. Subsequently, debinding is carried out, i.e. the binder, which is usually a polymer, is removed at high temperature, thereby obtaining a so-called "white body". During the debinding process, the binder is converted by thermal and / or thermochemical processes, the repeating units of the polymer are at least partially changed and at least partially decomposed into volatile components.
[0005] The white body is sintered at high temperature in a sintering furnace. Here, due to the temperature, the finely dispersed ceramic powder is compacted and solidified, thereby shrinking the porous component and increasing its strength.
[0006] However, the layer-by-layer construction method always has the disadvantage that during the heating process, especially during the debonding step, defects such as cracks or bubbles may form, which can make the component unusable. This effect can usually only be counteracted by slowing down the heating step, i.e. increasing the duration of the heat treatment, but this makes the corresponding production process uneconomical.
[0007] For example, US 5,496,682 discloses a curable composition for producing three-dimensional objects by stereolithography, the composition comprising 40 to 70 volume percent of ceramic particles or metal particles, 10 to 35 weight percent of a monomer, 1 to 10 weight percent of a photoinitiator, 1 to 10 weight percent of a dispersant, and preferably also comprising a solvent, a plasticizer and a coupling agent.
[0008] EP 2 233 449 A1 discloses a slurry for producing ceramic moldings by hot melt inkjet printing, which contains ceramic particles and at least one wax that can be polymerized by free radicals and gives a green body that can be debonded substantially without crack formation. However, in stereolithography methods, the slurry must remain in a stable liquid state for a long time, i.e. in particular the particles dispersed in the slurry must not settle prematurely, which poses a particular problem for the sought highest possible volume fraction of ceramic particles in the slurry.
[0009] EP 3 147 707 A1 discloses a method based on stereolithography which at least partially overcomes the above-mentioned disadvantages. However, here too, free-radical polymer precursors are used to produce the binder.
[0010] However, this free radical reaction also has disadvantages, since the free radicals may damage other components of the composition, especially in the case of silicate-based ceramic gels, thus causing discoloration. In addition, in free radical reactions with high conversion rates, an exponential increase in the reaction rate is also observed (Trommsdorff-Norrish effect). This effect is due to the reduced probability of chain breakage caused by the recombination of reactive chain ends, which in turn is caused by the increased immobility of the growing polymer chain. The increase in the exothermic reaction rate leads to an increase in temperature, thereby accelerating the decomposition of the free radical initiator and increasing the concentration of the reactive molecules. At the same time, due to the increased viscosity, the dissipation of the heat of reaction (polymerization heat) becomes more difficult. As a result, local overheating may occur, which in the case of layer-by-layer applied compositions may lead to cracks, explosions or decomposition of other components of the ceramic composition. The mechanical properties and durability of ceramic moldings obtained from known compositions are also limited, in particular due to their easy crack formation and decomposition. In addition, the stability / storage capacity of the ceramic composition is also limited.
[0011] Task
[0012] Against this background, the object of the present invention is therefore to provide a chemical combination which overcomes the above-mentioned disadvantages. The chemical combination according to the invention is intended to enable a problem-free construction method of ceramic gels or ceramic dispersions based on silicate minerals, from which ceramic moldings with high quality and low discoloration can be obtained.
[0013] Description of the invention
[0014] According to the invention, this object is achieved by a chemical combination for producing a ceramic gel, which comprises the following components:
[0015] A) a ceramic material, preferably in powder form, and
[0016] B) a binder, wherein:
[0017] The ceramic material comprises a silicate ceramic material or consists of a silicate ceramic material, and the binder comprises a gelling agent or consists of a gelling agent. Here, the gelling agent is preferably a polymer, wherein the polymer has one or more repeating units, wherein at least one of the one or more repeating units has at least one chelating functional group.
[0018] The chemical combination can be suitable for producing ceramic dispersions, in particular ceramic suspensions and / or ceramic gels. For this purpose, solvents and / or dispersants (such as water or alcohol) can preferably be added to the chemical combination, or the chemical combination has corresponding solvents and / or dispersants. The ceramic dispersion is preferably suitable for stereolithography methods, binder jetting or material jetting methods.
[0019] In colloid chemistry and process engineering, a dispersion is a heterogeneous mixture of at least two substances which are insoluble or barely soluble in one another or which are not chemically bound to one another. Here, one or more substances are finely dispersed as the so-called dispersed phase in another continuous substance, the so-called dispersion medium.
[0020] "Gel" is an example of a dispersed system consisting of at least two components. Here, the solid component, i.e., the gelling agent, forms a sponge-like three-dimensional network structure with its long molecules and / or highly branched molecules, the pores of which are filled with liquid (hydrogel (Lyogel)) or gas (xerogel (Xerogel)). As a result, the liquid component is fixed in the solid component. If the network structure is highly porous and stores air, the gel is also called an aerogel.
[0021] Gelling agents act as scaffolding agents and thicken the liquid phase and / or form a rubbery gel. Gelling agents can therefore also be used as thickeners or for stabilizing emulsions. A distinction can be made between natural gelling agents (e.g. agar), inorganic gelling agents (e.g. bentonite), semisynthetic gelling agents (e.g. carboxymethylcellulose) and synthetic gelling agents (e.g. polyvinyl alcohol). According to the invention, semisynthetic gelling agents and synthetic gelling agents are particularly preferred due to their high performance.
[0022] According to the invention, "solvent and / or dispersant" refers to a substance which is liquid under standard conditions (temperature: 298.15 K = 25°C, pressure: 1013.25 mbar = 1013.25 hPa) in which the components of the chemical combination can be at least partially dissolved and / or dispersed.
[0023] According to the invention, a "binder" is a substance or a combination of substances which, by holding together and stabilizing the ceramic particles, in particular during heat treatment, and by enabling a homogeneous distribution, enables the production of a stable dispersion or gel. As an essential component, the binder according to the invention has or consists of a gelling agent, for example a polymer with chelating functional groups. The binder according to the invention also helps to stabilize the fine distribution of the ceramic material in the solvent and / or dispersant, i.e., if a solvent and / or dispersant is used, the binder makes it more difficult for the ceramic material to settle or even completely prevents the ceramic material from settling.
[0024] In the context of the present invention, a "polymer" is understood to be a chemical substance consisting of macromolecules.
[0025] "Macromolecule" is a molecule composed of one or more identical or similar structural units, i.e. structural repeating units, (IUPAC. Compendium of Chemical Terminology, 2nd ed. (the "Gold Book"), AD McNaught, A. Wilkinson, Blackwell Scientific Publications, Oxford (1997), SJ Chalk. ISBN 0-9678550-9-8). Such macromolecules have more than 10 repeating units, preferably more than 15 repeating units. The molar mass is preferably at least 3000 g / mol, preferably at least 5000 g / mol, particularly preferably at least 7000 g / mol, and most preferably at least 10000 g / mol.
[0026] Polymers are usually prepared by reacting monomers or oligomers having one or more structural repeating units in a polymerization reaction. Here, an oligomer is a molecule formed from a plurality of monomers and thus composed of a plurality of structural units of identical or similar structure. Within the scope of the present invention, a molecule is referred to as an oligomer if it is formed by the reaction of 2 to 10, preferably 2 to 8, preferably 3 to 7 monomers.
[0027] Preferably, the adhesive has more than 50 weight percent, preferably more than 70 weight percent, even more preferably more than 80 weight percent, even more highly preferably more than 90 weight percent, and most preferably more than 95 weight percent or even 100 weight percent of gelling agent, which is preferably in the form of a polymer having chelating functional groups.
[0028] Preferably, the ceramic material has more than 50 weight percent, preferably more than 70 weight percent, even more preferably more than 80 weight percent, even more highly preferably more than 90 weight percent, and most preferably more than 95 weight percent silicate ceramic material.
[0029] Silicate ceramic materials are inorganic non-metallic materials produced from silicate raw materials (i.e., containing [SiO4] in the crystal structure). 4 The silicate ceramic material is preferably obtained from a tetrahedral compound. The proportion of SiO2 in the silicate ceramic material is preferably ≥20 weight percent, more preferably ≥30 weight percent. The term silicate ceramic material may also include glass ceramics. However, glass ceramics are preferably not included. The proportion of glass ceramics in the silicate ceramic material is preferably less than 5 weight percent, more preferably less than 2 weight percent, even more preferably less than 1 weight percent, even more preferably less than 0.5 weight percent, and most preferably less than 0.1 weight percent.
[0030] According to the invention, the term "chemical combination" is understood to mean a predetermined combination of individual chemicals which are present in separate containers or are partially or completely premixed in a composition. Particularly preferably, the chemical combination is present in the form of a composition, in particular in the form of a liquid, pasty or solid composition.
[0031] "Chelate functional group" is understood as a functional group that can form a chelate. A chelate is a cyclic coordination compound having at least one central metal atom or central metal ion and a multidentate ligand (so-called chelate ligand). A ligand is an ion or molecule that can bind to a central metal atom or central metal ion through a coordination bond, i.e., coordinate. The difference between a coordination bond and a classical covalent bond is that the ligand provides two bonding electrons in the coordination bond, so the ligand is a "Lewis base". In this case, multidentate means that the ligand has two or more coordination sites, through which the ligand coordinates to a metal atom or metal ion. In other words, a chelate ligand must have two or more atomic groups that can act as electron donors.
[0032] In a preferred embodiment of the present invention, the chelating ligand has three or more, more preferably four or more, particularly preferably five or more, and most preferably six or more coordination sites.
[0033] The inventors have observed that by using the gelling agents according to the invention, for example polymers with chelating groups, it is possible to produce silicate ceramic dispersions or silicate ceramic gels which have ceramic particles of high stability, i.e. which do not show a tendency to segregate or only show a very low tendency to segregate. Furthermore, the compositions have a structure which is easy to process but at the same time sufficiently stable. This has not been possible before, or has been achieved only to an insufficient extent.
[0034] In particular, when using polymers with chelating groups, the inventors, without being bound by theory, assume that the chelating groups form polar interactions with the partially positively charged silicon atoms of the silicate ceramic, which can achieve stabilization, in particular in dispersions. The polymer material having at least one chelating functional group thus acts as a binder. Since the corresponding polymer material also increases the viscosity of the gel or dispersion, a flowable and easily processable, in particular sprayable, material can be obtained. As a result, the necessity of using free-radically polymerizable polymer precursor compounds in production to ensure the processability of the corresponding ceramic gel is eliminated.
[0035] Using the chemical combination according to the invention, ceramic gels or ceramic dispersions can be produced, which can also be used to build extremely fine and small-sized structures. In addition, during debinding and sintering, smaller edge shrinkages, i.e. less pronounced volume changes, can be observed. The inventors believe that this is due to the uniform distribution of the ceramic particles in the gel. In addition, debinding is also particularly efficient and rapid.
[0036] In order to achieve particularly good processability of the gel or dispersion, the gel or dispersion preferably has an increased viscosity. To achieve this, in a preferred embodiment of the invention, it is advantageous if the gelling agent is a crosslinked polymer, more precisely, the macromolecules of the polymer of the chemical combination are crosslinked.
[0037] Preferred gelling agents are selected from the group consisting of: polysaccharides, such as chitosan or chitosan derivatives, alginic acid, xanthan gum or alginates; polyuronic acid; gelatin; hyaluronic acid; polyvinyl alcohol, polyethylene glycol; ammonium acryloyldimethyltaurate; hydroxypropyl starch (HPS); hydroxypropyl distarch phosphate (HDP); polyquaternary ammonium salts, in particular 3-methyl-1-vinylimidazolylmethylsulfate-N-vinylpyrrolidone copolymer, or poly (2-methacryloyloxyethyltrimethylammonium chloride); bentonite; sorbitan monooleate; polyethylene glycol triether or polypropylene glycol triether; propylene glycol dicaprylate / dicaprylate Decanoates; silicate clays and / or layered silicates, for example sodium magnesium silicate or aluminum magnesium silicate, sodium magnesium montmorillonite type layered silicates or sodium magnesium fluorohectorite type layered silicates; polyacrylamide; silica, such as Aerosil; sorbitan oleate decyl glucoside crosspolymer; styrene-maleic anhydride or ethylene-maleic anhydride copolymers and their derivatives; hydrophobically modified ethoxylated polyurethanes; polyvinylpyrrolidone; pullulan; cellulose or cellulose derivatives, such as cellulose acetate butyrate; polyacrylates or polymethacrylates and their esters, copolymers and / or salts; or mixtures and copolymers thereof. The above gelling agents are preferably crosslinked, in particular covalently crosslinked.
[0038] Particularly preferably, the gelling agent is a polymer that forms a hydrogel. A hydrogel is a gel formed by a water-insoluble polymer that can bind water. The molecules that make up the gel are chemically (e.g., by covalent bonds, supramolecular bonds or ionic bonds) or physically (e.g., by entanglement of polymer chains) connected to form a network structure that can bind a solvent (e.g., water). For example, a covalently cross-linked polymer is a thiomer, which cross-links the polymer chains by forming disulfide bridges.
[0039] A preferred special form of gelling agent is a super absorbent polymer. Super absorbent polymers ("superabsorbents") are preferably crosslinked polymers that are able to absorb several times their own weight of solvents, in particular polar solvents, such as water. When liquid is absorbed, the superabsorbent swells and forms a hydrogel. The working principle of super absorbent polymers is described, for example, in Koltzenburg, S., Nuyken, O., Maskos, M. (2013). Polymere: Synthese, Eigenschaften und Anwendungen. Deutschland: Springer Berlin Heidelberg.
[0040] According to the invention, the superabsorbent polymer is preferably a copolymer having repeating units of acrylic acid and / or sodium acrylate and / or acrylic ester, preferably a crosslinked copolymer.
[0041] According to the invention, the superabsorbent polymer is preferably a copolymer having repeating units of methacrylic acid and / or sodium methacrylate and / or methacrylate esters, preferably a crosslinked copolymer.
[0042] Crosslinked copolymers of acrylic acid and sodium acrylate or crosslinked copolymers of acrylic acid and / or sodium acrylate and / or acrylamide, in particular crosslinked copolymers of acrylic acid and sodium acrylate and acrylamide, are particularly preferred.
[0043] Crosslinked copolymers of methacrylic acid and sodium methacrylate or crosslinked copolymers of methacrylic acid and / or sodium methacrylate and / or methacrylamide, in particular crosslinked copolymers of methacrylic acid and sodium methacrylate and methacrylamide are particularly preferred. The corresponding copolymers crosslinked with sucrose allyl ether or pentaerythritol aryl ether are particularly preferred.
[0044] Carbomers are particularly preferred, especially because of their wide range of applications and good availability, especially carbomers crosslinked with polyols, polyol enol ethers, such as polyol allyl ethers or polyol enol ethers of sugars, sucrose allyl ethers or pentaerythritol allyl ethers.
[0045] In addition, it has been shown that polymers in which the chelating group comprises one or more oxygen atoms are particularly preferred in applications. The inventors believe that the stabilizing effect is particularly high due to the particularly pronounced Si-O interaction. For example, the chelating group can be an acid, salt or ester group, such as in polyacrylic acid or polyacrylate. Polyvinyl pyrrolidone or polyvinyl phosphonate have also been shown to be particularly preferred. Particularly preferably, the macromolecules of the above-mentioned polymers are cross-linked, preferably covalently cross-linked. The terms "cross-linking" and "cross-linking" are used synonymously here and represent that multiple macromolecules of a polymer are connected into a three-dimensional network structure. Cross-linking can be achieved directly during the macromolecular formation process or by reacting with an existing polymer. Thus, the expansion of the polymer is observed, which in turn has a positive effect on the dispersion medium regulation.
[0046] Preferably, the chemical combination has a content of polymerizable polymer precursor compounds (e.g., monomers or oligomers) of less than 5 weight percent, preferably less than 2 weight percent, even more preferably less than 1 weight percent, even significantly more preferably less than 0.5 weight percent, and most preferably less than 0.1 weight percent.
[0047] Particularly preferably, the weight ratio of polymerizable polymer precursor compound to polymer in the chemical combination is 1:10 or more, preferably 1:50 or more, and particularly preferably 1:100 or more.
[0048] The correspondingly low proportion of polymerizable compounds prevents side reactions and decomposition reactions during gel production.
[0049] Preferably, the binder and / or gelling agent has a low ash residue, preferably ≤10 weight percent, more preferably ≤5 weight percent, even more preferably ≤1 weight percent, even significantly more preferably ≤0.5 weight percent, and most preferably ≤0.2 weight percent ash residue.
[0050] The determination of the ash residue, ie the residue remaining after the ash heat treatment, can be carried out as described in DIN EN ISO 3451-1, in particular by means of thermogravimetric analysis. A low ash residue ensures a low degree of discoloration of the ceramic molding.
[0051] Preferably, the chemical combination according to the invention also has a solvent and / or a dispersant. In this case, in particular polar and / or protic solvents, such as water and / or alcohols, in particular polyols, such as ethylene glycol or monopropylene glycol, are preferred. These solvents are particularly suitable for keeping the components of the gel or dispersion obtained from the chemical combination in a dispersed or dissolved form, thereby achieving processability of the gel or dispersion.
[0052] In a preferred embodiment of the present invention, the weight proportion of the solvent and / or dispersant in the weight of the chemical combination is at least 5 weight percent, preferably at least 10 weight percent, even more preferably at least 15 weight percent, even more preferably at least 20 weight percent, even significantly more preferably at least 30 weight percent, and most preferably at least 40 weight percent, but typically ≤70 weight percent.
[0053] Excluding the weight of the ceramic material, the weight of the solvent and / or dispersant in the chemical combination is preferably 50 weight percent to 99.9 weight percent, more preferably 70 weight percent to 99 weight percent, and most preferably 90 weight percent to 99 weight percent.
[0054] In a preferred embodiment of the present invention, the weight proportion of ceramic material in the weight of the chemical combination is ≤70 weight percent, preferably ≤50 weight percent, even more preferably ≤40 weight percent, even more preferably ≤35 weight percent, and most preferably ≤30 weight percent, but preferably ≥20 weight percent.
[0055] In a preferred embodiment of the present invention, the weight proportion of ceramic material in the weight of the chemical combination is in the range of 5-70 weight percent, preferably in the range of 10-50 weight percent, even more preferably in the range of 15-40 weight percent, and most preferably in the range of 20-35 weight percent.
[0056] By means of a suitably low proportion of ceramic material, it is generally possible to produce gels which are flowable and therefore easy to handle.
[0057] Particularly preferably, the composition further comprises one or more bases, in particular Bronsted bases, i.e. compounds with a monomolar aqueous solution pH value of >7, preferably >8. The base ensures an improved interaction between the ceramic particles and the polymer material. In particular, in the case where the chelating group has an acid function, the base serves to trap protons, thereby further enhancing the complexing strength of the chelating group. This effect is particularly evident in polyacrylic acid or polyacrylates and polyvinylphosphonic acid or polyvinylphosphonic acid. Particularly preferably, the base is selected from the group consisting of alkali metal hydroxides and alkaline earth metal hydroxides and alkali metal carbonates and alkaline earth metal carbonates. Particularly preferably, the base is selected from the group consisting of NaOH, KOH, Na2CO3, K2CO3, CaCO3, CaO and Ca(OH)2, NaHCO3 or a mixture of the above substances.
[0058] Preferably, the chemical combination has an alkali content of ≤15 weight percent, more preferably less than 10 weight percent, even more preferably ≤5 weight percent, even more preferably ≤1 weight percent, and most preferably ≤0.5 weight percent. The minimum alkali content is preferably ≥0.05 weight percent, more preferably ≥0.1 weight percent.
[0059] The weight of the alkali in the weight of the chemical combination excluding the weight of the ceramic material is preferably 0.10 to 0.99 weight percent, more preferably 0.20 to 0.8 weight percent, and most preferably 0.3 to 0.7 weight percent.
[0060] In a preferred embodiment of the present invention, the chemical combination includes a preservative as an additional component, which is preferably biocidal. The preservative is used to increase the durability of the ceramic gel or ceramic dispersion, especially by preventing the decomposition process. Preferably, a sulfur-containing preservative is used as a preservative, particularly an isothiazolinone preservative. Due to their bactericidal and fungicidal effects, the components of the chemical combination can be protected from microbial decomposition. 5-chloro-2-methyl-4-isothiazoline-3-one, 2-methyl-4-isothiazoline-3-one, isothiazolinone-3-one, methylisothiazolinone, benzisothiazolinone, octylisothiazolinone, dichlorooctylisothiazolinone or a mixture of the foregoing substances is particularly preferred. Alternatively, formaldehyde releasers (such as O-formaldehyde or N-formaldehyde) are also suitable for use as preservatives. Formaldehyde benzyl alcohol hemiacetal, 1,6-dihydroxy-2,5-dioxane, methyl urea, 7-ethylbicyclooxazolidine, urotropine, paraformaldehyde, tris(hydroxymethyl)nitromethane or a mixture of the above substances.
[0061] The chemical combination preferably has a preservative content of ≤5 weight percent, more preferably ≤2 weight percent, even more preferably ≤1 weight percent, even significantly more preferably ≤0.5 weight percent, and most preferably ≤0.25 weight percent. The minimum preservative content is preferably ≥0.05 weight percent, more preferably ≥0.1 weight percent.
[0062] In order to control the coloring of the ceramic gel or ceramic dispersion, the chemical combination can also include a coloring component, which is preferably selected from transition metal compounds, especially oxides, such as Er2O3, Fe2O3, Co3O4, MnO2, NiO2, Cr2O3, Pr2O3, Tb2O3, Bi2O3 and mixtures of the above substances. However, alternatively or additionally, acetylacetonates or carboxylates of iron, cerium, praseodymium, nickel, terbium, lanthanum, tungsten, osmium, terbium and manganese can also be used.
[0063] Preferably, the coloring component is selected such that after debinding and sintering, a tooth-colored ceramic molding is obtained.
[0064] Coloring components may also be preferably contained in the ceramic material.The ceramic material may also contain other additives, such as flow agents or mold release agents.
[0065] Preferably, the chemical combination has a coloring component content of less than 5 weight percent, more preferably ≤2 weight percent, even more preferably ≤1 weight percent, even more preferably ≤0.5 weight percent, and most preferably ≤0.25 weight percent. The minimum coloring component content is preferably ≥0.05 weight percent, more preferably ≥0.1 weight percent.
[0066] In a preferred embodiment of the present invention, the weight proportion of ceramic material in the weight of the chemical combination is at least 40 weight percent, preferably at least 50 weight percent, even more preferably at least 55 weight percent, even more highly preferably at least 60 weight percent, and most preferably at least 65 weight percent.
[0067] In a preferred embodiment of the present invention, the weight proportion of ceramic material in the weight of the chemical combination is at most 95 weight percent, preferably at most 90 weight percent, even more preferably at most 85 weight percent, even more highly preferably at most 80 weight percent, and most preferably at most 75 weight percent.
[0068] In a preferred embodiment of the present invention, the weight proportion of ceramic material in the weight of the chemical combination is in the range of 50 to 90 weight percent, preferably in the range of 55 to 85 weight percent, even more preferably in the range of 60 to 80 weight percent, and most preferably in the range of 65 to 75 weight percent.
[0069] With a suitably high proportion of ceramic material, very dense gels with low ash residues can generally be obtained.
[0070] Furthermore, a correspondingly high proportion of ceramic material significantly reduces the probability of mechanical damage during the thermal treatment of the ceramic gel or dispersion and results in more homogeneous ceramic moldings.
[0071] In a preferred embodiment of the present invention, the weight proportion of the gelling agent (e.g., a gelling agent in the form of a polymer) in the weight of the chemical combination is ≥ 0.1 weight percent, more preferably ≥ 0.2 weight percent, even more preferably ≥ 0.5 weight percent, even more preferably at least 1 weight percent, even significantly more preferably at least 1.5 weight percent, even significantly more preferably at least 2 weight percent, and most preferably at least 2.5 weight percent. As a result, the ceramic material in the ceramic gel or ceramic dispersion is particularly significantly stabilized. However, preferably, the weight proportion of the polymer is not higher than 3.5 weight percent or 4 weight percent, so that when the chemical combination is subjected to heat treatment, as little ash residue as possible is generated.
[0072] Preferably, excluding the weight of the ceramic material, the weight of the gelling agent in the weight of the chemical combination is 0.10 weight percent to 0.99 weight percent, more preferably 0.20 weight percent to 0.8 weight percent, and most preferably 0.3 weight percent to 0.7 weight percent.
[0073] The weight ratio of the ceramic material to the weight of the other components of the chemical combination is preferably in the range of 1: 1 to 5: 1, more preferably in the range of 2: 1 to 4: 1, and most preferably in the range of 3: 1 to 4: 1. A ratio of ceramic powder to binder of 60: 40 to 70: 30 is also very preferred.
[0074] Preferably, the silicate ceramic is selected from the group consisting of: feldspar ceramics, leucite ceramics, lithium silicate ceramics, lithium disilicate ceramics and lithium aluminosilicate ceramics. Feldspar ceramics are particularly preferred, especially in combination with polyacrylic acid and / or polyacrylate as polymer. In this combination, a particularly pronounced stabilizing effect is observed.
[0075] The present invention also relates to a composition, in particular a gel or dispersion, consisting of or comprising the chemical combination. Preferably, the weight proportion of the chemical combination in the total weight of the composition is 10-70 weight percent, preferably 15-70 weight percent, even more preferably 20 to 60 weight percent, even more highly preferably 25 to 60 weight percent, and most preferably 30 to 60 weight percent.
[0076] Preferably, the gel or dispersion is prepared by mechanically mixing component B) (ie the binder) and optionally included ingredients (eg C) or E)) with a ceramic material, which is preferably in the form of a ceramic powder.
[0077] The invention also relates to a method for producing a ceramic molding, the method comprising or consisting of the following steps:
[0078] a1) mixing the components of the chemical combination defined above to obtain a gel or a dispersion,
[0079] b) irradiating or heat treating the gel or dispersion at a temperature ranging from 50° C. to 150° C. to obtain a green body,
[0080] c) at least partially, preferably completely, removing the binder, preferably by heat treating the green body at a temperature in the range of 150° C. to 350° C. or by irradiation, to obtain a white body,
[0081] d) sintering the white body, or if steps b) and / or c) are optional, the green body or the gel or the dispersion by heat treatment in a temperature range of 700° C. to 1000° C., to obtain a ceramic moulding.
[0082] These method steps are preferably carried out in sequence a1) to d) at different times.
[0083] The above steps b) and c) are optional and can be carried out together, i.e. in one step without a time interval. The production of the ceramic molding can also be carried out without the intermediate step of producing a green body or a white body. The binder is then removed in step d). However, when these steps are carried out, a particularly high product quality is obtained.
[0084] Preferably, the method according to the invention for producing a ceramic molding comprises the following additional steps:
[0085] a2) Applying the gel or dispersion layer by layer onto a surface, preferably onto a metal crown or zirconium oxide crown or an onlay post, wherein the application is preferably carried out by means of spraying technology and / or a 3D printing method, particularly preferably by means of Multijet modeling.
[0086] This step is preferably carried out between steps a1) and b) and is particularly preferably spaced apart in time from these steps.
[0087] Preferably, steps a2) and / or b) and / or c) and / or d) of the method according to the invention are carried out in a rapid prototyping method, in particular in a stereolithography method.
[0088] The invention also relates to ceramic moldings such as crowns, crown parts, veneers, ceramic inlays or ceramic onlays, bridge anchoring crowns, bridge connections and parts of the aforementioned parts produced by the method according to the invention. By using the chemical combination according to the invention in the above-mentioned method, ceramic moldings with particularly high homogeneity and natural appearance are obtained. Therefore, compared with the ceramic moldings known from the prior art, the ceramic moldings according to the invention show preferred properties. Using the gel according to the invention or the dispersion according to the invention, preferably by heat treatment of the green body in a temperature range of 150° C. to 350° C. or by radiation (especially infrared radiation) to obtain a white body, the binder can be removed particularly quickly and uniformly. In the above-mentioned temperature range, the debonding time can reach ≤20 minutes, ≤15 minutes, or even ≤10 minutes.
[0089] Furthermore, the ceramic molded bodies produced according to the method of the invention are characterized by high strength and high detail accuracy. According to ISO 6872, the flexural strength of the molded bodies made of feldspar ceramics or glass ceramics is preferably more than 50 MPa, in particular in the range of 100 to 500 MPa.
[0090] The invention also relates to the use of a composition consisting of a silicate ceramic and a gelling agent, in particular a polymer having one or more repeating units, at least one of which has at least one chelating functional group, in a gel for producing ceramic mouldings, preferably for producing ceramic mouldings for dental restorations, such as inlays, onlays, veneers, crowns, bridges or coverings thereon.
[0091] The invention further relates to the use of a gelling agent as a binder in a gel or dispersion for producing ceramic moldings, wherein the gel preferably comprises a silicate ceramic or consists of a silicate ceramic.
[0092] The invention also relates to the use of a polymer having one or more repeating units, wherein at least one repeating unit comprises at least one chelating function, as a binder in a gel or dispersion for producing ceramic moldings, wherein the gel preferably comprises or consists of a silicate ceramic.
[0093] Example
[0094] The invention will now be described exemplarily on the basis of specific embodiments and corresponding photographic illustrations.
[0095] Production Example 1
[0096] Produce a mixture of the following components in a petri dish:
[0097] 1) Deionized water (about 70 weight percent)
[0098] 2) Carbomer (about 17 weight percent)
[0099] 3) Sodium hydroxide (about 3 weight percent)
[0100] 4) Monopropylene glycol (about 7 weight percent)
[0101] 5) A mixture of 5-chloro-2-methyl-4-isothiazolin-3-one, 2-methyl-4-isothiazolin-3-one and isothiazolinone-3-one (the remainder)
[0102] After obtaining a homogeneous slurry, feldspar ceramic powder or glass ceramic powder is mixed into the mixture. 3-4 times the amount of ceramic powder is added relative to the sum of the masses of the mixture with components 1) to 5) so that a sprayable ceramic dispersion is obtained after mechanical mixing. The mass is transferred to a 10 ml syringe from Coltene and then applied layer by layer to the stent body. Then a heat treatment is carried out at 150°C to obtain a green body. Subsequently, a heat treatment is carried out at 300°C to obtain a white body, which is then fired at 950°C.
[0103] Production Example 2
[0104] Produce a mixture of the following components in a petri dish:
[0105] 1) Deionized water (about 98.5 weight percent)
[0106] 2) Carbomer (about 1.0 weight percent)
[0107] 3) Potassium hydroxide (about 0.5 weight percent)
[0108] After obtaining a homogeneous slurry, feldspar ceramic powder or glass ceramic powder is mixed into the mixture. 3-4 times the amount of ceramic powder is added relative to the sum of the mass of the mixture with components 1) to 3) so that a sprayable ceramic dispersion is obtained after mechanical mixing. The mixture is transferred to a 10 ml syringe from Coltene and then applied layer by layer to the stent body. Then a heat treatment is carried out at 150°C to obtain a green body. Subsequently, a heat treatment is carried out at 300°C to obtain a white body, which is then fired at 950°C.
[0109] Figure 1 A photographic illustration of a white body before firing obtained by the above-mentioned method "Production Example 1" is shown.
[0110] Figure 2 The same white tire is shown after firing at 950°C for 60 minutes. Figure 2 It can be seen that a homogeneous ceramic component with a closed structure is obtained.
Claims
1. A chemical combination comprising the following components: A) a ceramic material, which comprises a silicate ceramic material or consists of a silicate ceramic material, B) adhesive, It is characterized in that The adhesive comprises a gelling agent or consists of a gelling agent.
2. The chemical combination according to claim 1, wherein: The gelling agent comprises or consists of a polymer, the polymer comprising one or more repeating units, wherein preferably at least one of the one or more repeating units has a chelating functional group.
3. The chemical combination according to claim 2, wherein: The polymers are cross-linked.
4. The chemical combination according to any one of claims 2 or 3, wherein: The polymer is a superabsorbent polymer, preferably a copolymer having repeating (meth)acrylic acid units and / or repeating sodium (meth)acrylate units.
5. A chemical combination according to any one of the preceding claims, wherein: The combination comprises the following additional components: C) A solvent and / or a dispersant, which is preferably selected from the group consisting of water and alcohols.
6. A chemical combination according to any one of the preceding claims, wherein: The combination comprises the following additional components: D) A base, which is preferably selected from the group consisting of alkali metal hydroxides and alkaline earth metal hydroxides and alkali metal carbonates and alkaline earth metal carbonates.
7. A chemical combination according to any one of the preceding claims, wherein: The combination comprises the following additional components: E) Preferably a biocidal preservative.
8. A chemical combination according to any one of the preceding claims, wherein: The combination comprises the following additional components: F) A coloring component, which is preferably selected from the following: Er2O3, Fe2O3, Co3O4, MnO2, NiO2, Cr2O3, Pr2O3, Tb2O3, Bi2O3 and mixtures thereof.
9. A chemical combination according to any one of the preceding claims, wherein: The weight of the ceramic material accounts for a proportion of the weight of the chemical combination in a range of 50 to 90 weight percent, preferably in a range of 60 to 80 weight percent.
10. A chemical combination according to any one of the preceding claims, wherein: The silicate ceramic material is selected from the group consisting of feldspar ceramics, leucite ceramics, lithium silicate ceramics, lithium disilicate ceramics and lithium aluminosilicate ceramics.
11. A gel or dispersion comprising a chemical combination as defined in any one of the preceding claims.
12. A method for producing a ceramic molded part, the method comprising the following steps: a1) mixing the components of the chemical combination as defined in any one of the preceding claims to obtain a gel or a dispersion, b) optionally: heat treating the gel or the dispersion at a temperature ranging from 50° C. to 200° C. to obtain a green body, c) optionally: removing the binder by heat treating the green body at a temperature ranging from 250° C. to 350° C. to obtain a white body, d) sintering by heat treatment at a temperature ranging from 700° C. to 1000° C. to obtain a ceramic molded part.
13. A method for producing a ceramic moulding comprising the additional steps of: a2) Applying the gel or dispersion to the surface layer by layer, preferably by spraying technology and / or 3D printing methods, particularly preferably by means of binder jetting, material jetting, Polyjet modeling or Multijet modeling.
14. A ceramic moulding obtained by a method as defined in claim 12 or 13.
15. Use of a composition consisting of a silicate ceramic material and a polymer in a gel or dispersion for producing a ceramic moulding, preferably for producing a ceramic moulding for a dental restoration such as an inlay, onlay, veneer, crown or bridge, the polymer comprising repeating units having at least one chelating functional group.
Citation Information
Patent Citations
Slip for the production of dental ceramics with hot melt inkjet printing methods
EP2233449A1
Three dimensional sintered inorganic structures using photopolymerization
US5496682A
Dental appliance, process for producing a dental appliance and use thereof
CN102223853A
Additive fabrication of proppants
CN105451950A
Ceramic and glass ceramic slip for stereolithography
CN108027554A